EFEK KOMITMEN MANAJEMEN PUNCAK TERHADAP PERILAKU PELAYANAN KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Nina Agustina; Andreas W. Gunawan Putra (Jurnal Manajemen dan Pemasaran Jasa, 2011)
The purpose of this paper is to examine the impact of management commitment to service on employee service behaviors and to develop and test a conceptual model of the antecedents and consequences of job satisfaction in the hospitality industry. The conceptual framework consists ofthe following constructs: management support, reward, empowerment, training, job satisfaction, extra role customer service behavior and cooperation. Moreover, six (6) hypotheses were developed and tested. Instrument test of validity and reliability used to test the validity of themeasures, while multiple regression was used in hypotheses testing. Data were collected from110 respondent who are working at Sekolah Dian Harapan Daan Mogot, Jakarta Barat. Strong support was found for 1 of the 6 hypotheses. Findings reveal that management support has positive effects on job satisfaction. It is shown that reward, empowerment, training are notrelated to job satisfaction. Moreover, it is demonstrated that the two dimensions of service behavior – extra-role customer service behaviors and cooperation also are not related to jobsatisfaction. Importantly, it is found that job satisfaction can be created from employee servicebehavior as the school is applying the management support to the employees.Keywords: school, management commitment, management support, employee job satisfaction,service behaviors